Phenotypic Characterization of Pore Mutants of the Vibrio cholerae Porin OmpU - Pagel, Melissa (American Society for Microbiology (ASM), 2007)
General-diffusion porins form large β-barrel channels that control the permeability of the outer membrane of gram-negative bacteria to nutrients, some antibiotics, and external signals. Here, we have analyzed the effects of mutations in the OmpU porin of Vibrio cholerae at conserved residues that are known to affect pore properties in the Escherichia coli porins OmpF and OmpC. Various phenotypes were investigated, including sensitivity to β-lactam antibiotics, growth on large sugars, and sensitivity to and biofilm induction by sodium deoxycholate, a major bile component that acts as an external signal for multiple cellular responses of this intestinal pathogen. Overall, our results indicate that specific residues play different roles in controlling the passage of various compounds. Mutations of barrel wall arginine residues that protrude in the pore affect pore size and growth in the presence of large sugars or sodium deoxycholate. Sensitivity to large cephalosporins is mostly affected by D116, located on the L3 loop, whose homolog in E. coli, OmpF, is a known binding determinant for these drugs. L3 loop residues also affect biofilm induction. The results are interpreted in terms of a homology model based on the structures of E. coli porins.